Assessing the Adequacy of Natural Science Information: A Bayesian Approach - Adams, Richard M.; Crocker, Thomas D.; Katz, Richard W. (The Review of Economics and Statistics, 1984)
Richard M. Adams, Thomas D. Crocker, Richard W. Katz, Assessing the Adequacy of Natural Science Information: A Bayesian Approach, The Review of Economics and Statistics, Vol. 66, No. 4 (Nov., 1984), pp. 568-575